Ceftaroline in the management of complicated skin and soft tissue infections and community acquired pneumonia - Mpenge MA; MacGowan AP (Dove Medical Press, 2015)
Mbiye A Mpenge,1 Alasdair P MacGowan2 1Department of Medical Microbiology, University Hospitals Bristol NHS Trust, Bristol Royal Infirmary, Bristol, England; 2Department of Medical Microbiology, North Bristol NHS Trust, Southmead Hospital, Bristol, England Abstract: Ceftaroline is a new parenteral cephalosporin approved by the European Medicines Agency (EMA) and the US Food and Drug Administration (FDA) for the treatment of complicated skin and soft tissue infections (cSSTIs) including those due to methicillin-resistant Staphylococcus aureus (MRSA), and community-acquired pneumonia (CAP). Ceftaroline has broad-spectrum activity against gram-positive and gram-negative bacteria and exerts its bactericidal effects by binding to penicillin-binding proteins (PBPs), resulting in inhibition of bacterial cell wall synthesis. It binds to PBP 2a of MRSA with high affinity and also binds to all six PBPs in Streptococcus pneumoniae. In in vitro studies, ceftaroline demonstrated potent activity against Staphylococcus aureus (including MRSA and vancomycin-intermediate isolates), Streptococcus pneumoniae (including multidrug resistant isolates), Haemophilus influenzae, Moraxella catarrhalis, and many common gram-negative pathogens, excluding extended spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae and Pseudomonas aeruginosa. In Phase II and Phase III clinical trials, ceftaroline was noninferior to its comparator agents and demonstrated high clinical cure rates in the treatment of cSSTIs and CAP. It demonstrated favorable outcomes in patients treated for both regulatory-approved indications and unlicensed indications in a retrospective analysis. Ceftaroline is a safe and effective option for treatment in specific patient populations in which its efficacy and safety have been proven. This article reviews the challenges in the treatment of cSSTI and CAP, ceftaroline and its microbiology, pharmacology, efficacy, and safety data which support its use in treatment of cSSTIs and CAP. Keywords: ceftaroline, cephalosporin, cSSTI, CAP, Staphylococcus aureus, Streptococcus pneumoniae